2012
DOI: 10.3389/fonc.2012.00168
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate receptors and sphingosine kinase 1: novel biomarkers for clinical prognosis in breast, prostate, and hematological cancers

Abstract: There is substantial evidence for a role in cancer of the bioactive lipid sphingosine 1-phosphate (S1P), the enzyme sphingosine kinase 1 (that catalyses S1P formation) and S1P-specific G protein-coupled receptors. This perspective highlights recent findings demonstrating that sphingosine kinase 1 and S1P receptors are new important biomarkers for detection of early cancer and progression to aggressive cancer. The impact of the sub-cellular distribution of S1P metabolizing enzymes and S1P receptors and their sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The PI3K/AKT pathways are also involved in crosstalk with RAS/RAF/MEK/ERK and estrogen receptor pathways [45]. As S1P has emerged as a new class of lipid messengers that regulate cell proliferation, differentiation, and migration in vitro [68] and also in clinical samples, we became interested to understand whether blocking of both sphingosine kinases inhibited MAPK cascades and PI3K/AKT pathways in metastatic breast cancer LM2-4 cells. In agreement with earlier reports [7,46], extracellular S1P or EGF activates P-ERK, P-p38, P-AKT, and P-p70S6K in MCF-7 cells and inhibiting SphKs activity with DMS [36] attenuated EGF-mediated survival signaling (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PI3K/AKT pathways are also involved in crosstalk with RAS/RAF/MEK/ERK and estrogen receptor pathways [45]. As S1P has emerged as a new class of lipid messengers that regulate cell proliferation, differentiation, and migration in vitro [68] and also in clinical samples, we became interested to understand whether blocking of both sphingosine kinases inhibited MAPK cascades and PI3K/AKT pathways in metastatic breast cancer LM2-4 cells. In agreement with earlier reports [7,46], extracellular S1P or EGF activates P-ERK, P-p38, P-AKT, and P-p70S6K in MCF-7 cells and inhibiting SphKs activity with DMS [36] attenuated EGF-mediated survival signaling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finding strategies to cure metastatic TNBC would be beneficial for breast cancer patients. Sphingosine-1-phosphate (S1P) is a potent bioactive lipid mediator produced by the cytosolic SphK1 and the nuclear localized SphK2 from the substrate sphingosine [5], has been known to play important roles to cancer development and progression by regulating tumor proliferation, migration and angiogenesis [69]. Although some important roles of intracellular actions of S1P have been discovered [5,10,11], the majority of its biological functions are known to mediated by plasma membrane localized family of five specific G protein coupled receptors (S1PR1-5) [8,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies demonstrated that cancer cells can secrete S1P ( 54,76,77 ). Moreover, data from preclinical mouse cancer models ( 37,78 ) and human patient samples ( 35,36,79 ) suggest that the tumors themselves with upregulated SphK1 may be a key source of S1P. However, Hla and colleagues ( 51 ) reported that endothelial cells (human umbilical vein vascular endothelial cells and mouse embryonic endothelial cells) synthesize and release endogenous S1P more effi ciently than human colon cancer cell lines.…”
Section: Tumor-induced Angiogenesis By Inside-out Signaling Of S1pmentioning
confidence: 96%
“…Therefore, the S1P 4 -HER2 signalling platform enhances signalling gain in response to S1P (Figure 1); this is significant as ERK-1/2 is implicated in promoting metastasis. Indeed, high S1P 4 expression in tumours of ER negative breast cancer patients is also correlated with node positive status, suggesting a role for S1P 4 in metastasis (Ohotoski et al, 2012;Pyne et al, 2012). The link between S1P and metastasis is further evidenced by studies from Ponnusamy et al (2012), who demonstrated a reduction in systemic S1P inhibits TRAMP-induced prostate cancer growth in TRAMP +/+ Sk1 -/-mice or lung metastasis of various cancer cells in Sk1 -/-mice.…”
mentioning
confidence: 99%